Writing Strategies of Freshmen and Sophomore Students in a Tertiary Institution: Implications to English Teacher - Asio, John Mark; Mobo, Catherine; Anico, Mark Jaebel; Calderon, Arwill Antoine; Capistrano, Mika (Asian Journal of Applied Education (AJAE), 2023)
This research aims to determine students' writing strategies in a tertiary institution in Olongapo City, Philippines. Seventy-two (72) college freshmen and sophomore students participated in the study. The researchers used a standardized survey questionnaire to gather pertinent data. Also, the researchers calculated the descriptive and inferential statistics using SPSS 20. The study results revealed that the student respondents have a "neutral" response to the monitoring and planning for writing. On the other hand, the student-respondents gave an "agree" remark for the revising and thinking aspects of writing. Furthermore, the study also found significant differences in the writing strategies of the freshmen and sophomore students when grouped according to their sex regarding revising, thinking, and planning.